Invariant Spatial Pattern Across Mediterranean Scrublands in the Iberian Pear (Pyrus bourgaeana) - Brayan Morera; Pedro J. Garrote; Thorsten Wiegand; Daniel Ayllón; Jose M. Fedriani (Ecology and Evolution)
ABSTRACT The spatial distribution pattern of plant species is frequently driven by a combination of biotic and abiotic factors that jointly influence the arrival, establishment, and reproduction of plants. Comparing the spatial distribution of a target plant species in different populations represents a robust approach to identify the underlying mechanisms. We mapped all reproductive individuals of the Iberian pear (Pyrus bourgaeana) in five plots (1.39–8.57 km2) differing in the activity of seed dispersers and vertebrate herbivores in southern Iberian Peninsula. We used Thomas point process models to quantify the consistency in the spatial pattern and the level of spatial aggregation of this mammal‐dispersed tree among the five populations. We tested two hypotheses: (i) because the clumped defecation behavior of some dispersers can lead to local tree aggregation, and because denser groups of fruiting trees can limit seed dispersal by attracting frugivores to specific sites, we expected a consistent small‐scale aggregation pattern across all populations; and (ii) because ungulates reduce recruitment by preying on seeds and seedlings, we hypothesize that ungulate activity will show negative relationships with tree density and level of aggregation. Our spatial analysis revealed consistent and highly aggregated small‐scale patterns of all Iberian pear populations, with one critical scale aggregation, a low density of clusters and high variability in the number of trees per cluster. Ungulate activity and the number of trees per cluster showed a marginally significant negative correlation, suggesting that in areas with higher ungulate activity, trees tend to form less dense clusters. Although several of the underlying processes varied greatly among the five study sites, the Iberian pear showed a relatively consistent spatial pattern with just quantitative nuances throughout the entire region. This result has significant implications for the reproductive success of the species, management strategies, and ultimately the long‐term persistence of populations.